2015
DOI: 10.12809/hkmj144437
|View full text |Cite
|
Sign up to set email alerts
|

The safety and tolerability of adenosine as a pharmacological stressor in stress perfusion cardiac magnetic resonance imaging in the Chinese population

Abstract: Objective: To investigate the safety profile and effectiveness of adenosine as a pharmacological stressor in patients with known or suspected coronary artery disease who underwent cardiac magnetic resonance imaging perfusion study. Design: Case series.Setting: Regional hospital, Hong Kong. Patients:All patients who underwent adenosine stress cardiac magnetic resonance imaging from May 2013 to August 2013 were prospectively interviewed during the scan. Main outcome measures:Common side-effects of adenosine as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
5
0
2
Order By: Relevance
“…Sensitivity analysis involved the stepwise exclusion of individual studies from the analysis to assess their impact on the results. The pooled effects of OAC treatment on all-cause mortality were impacted by the exclusion of 2 studies [Ouellet ( 16 ) and Orkaby ( 8 )] and the effect on ischemic stroke was similarly influenced by the exclusion of 2 studies [Orkaby ( 8 ) and Subic ( 7 )]. The pooled effects of major bleeding remained unchanged with the omission of a single study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensitivity analysis involved the stepwise exclusion of individual studies from the analysis to assess their impact on the results. The pooled effects of OAC treatment on all-cause mortality were impacted by the exclusion of 2 studies [Ouellet ( 16 ) and Orkaby ( 8 )] and the effect on ischemic stroke was similarly influenced by the exclusion of 2 studies [Orkaby ( 8 ) and Subic ( 7 )]. The pooled effects of major bleeding remained unchanged with the omission of a single study.…”
Section: Resultsmentioning
confidence: 99%
“…The thermodilution-based index of microvascular resistance (T-IMR) is recommended as the gold standard for the invasive methods ( 7 ). However, T-IMR requires adenosine-induced hyperemia, which often introduces chest discomfort and dyspnea ( 8 ); the use of additional intra-vascular devices (pressure wire) increases the risk of coronary artery dissection; administering additional heparin to prevent thrombosis can also heighten the risk of hemorrhage. These limitations have restricted the widespread use of the T-IMR test.…”
Section: Introductionmentioning
confidence: 99%
“…ст.) [8,15,26]. Учет этих факторов позволяет снизить риск возникновения во время пробы клинически значимых осложнений и, соответственно, число случаев преждевременного прекращения пробы.…”
Section: противопоказания к пробе с атфunclassified
“…Для получения адекватной информации о состоянии регионального коронарного кровоснабжения во время нагрузочной пробы необходимо достижение уровня вазодилатации коронарного русла, приближающегося к максимальному [26,29,30]. Ранее было показано, что максимально возможное расширение КА при интракубитальном введении АТФ может быть получено только при введении препарата в дозе не менее 140 мкг / кг / мин, причем это состояние достигается не раньше чем через 2 мин от начала инфузии [13,21].…”
Section: начальная дозировка препаратаunclassified
“…Bruder et al also showed a very low rate of severe complications of stress CMR using adenosine and dobutamine, with a rate of 0.026% [ 4 ]. However, there are limited studies regarding the clinical impact and safety of stress CMR in Asia, and most of them were relatively small in scale [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%